Geostrategic Aspect of Passenger High-Speed Railway Communication - Савчук, І. (Київський національний університет імені Тараса Шевченка, 2016)
Geostrategic aspect of passenger high-speed railway communication is an important element of the national defense strategy. The use of this mode of transport creates new opportunities for moving troops and at the same time gives rise to certain problems with the placement of the respective units of the armed forces of the country. The questions of defense organization of infrastructure elements of high-speed railway communication and their deployment in residential places, especially in the cities are of great importance.

Геостратегічний аспект пасажирського високошвидкісного залізничного сполучення є важливим елементом національної стратегії оборони. Використання цього виду транспорту створює нові можливості щодо переміщення військовослужбовців та водночас породжує певні проблеми з розміщенням відповідних структурних елементів Збройних сил відповідної країни. Велике значення при цьому набувають питання організації оборони елементів інфраструктури високошвидкісного залізничного сполучення та їх дислокація у населених пунктах, особливо у містах.
Геостратегічний аспект пасажирського високошвидкісного залізничного сполучення
Keywords: геостратегія; високошвидкісне залізничне сполучення; пасажирські перевезення; geostrategy; high-speed railway communication; passenger transportation